Chromium levels in conilon coffee seedlings developed in substrate with tannery sludge as alternative manure - Berilli, Sávio Silva; Berilli, Ana Paula Candido Gabriel; Carvalho, Almy Júnior Cordeiro de; Freitas, Silvio de Jesus; Cunha, Maura; Fontes, Patrícia Soares Furno (Coffee Science - ISSN 1984-3909, 2015)
The use of by-products of the leather processing industries in agriculture represents a major breakthrough in production processes, nutrient cycling and agro-ecological awareness. However, the use of tannery sludge as seedling’s substrate shows the presence of chromium, considered a harmful element, under specific conditions, to the environment. The experiment was carried out at the Federal Institute of Education, Science and Technology of Espírito Santo - Campus Itapina, aiming to identify the levels of chromium accumulation in tissue, as well as, the development of conilon coffee seedlings that were propagated for four months in a greenhouse, in substrate enriched with tannery sludge as an alternative source of fertilizer. The experimental design consisted of randomized blocks, with five treatments, four ratios of soil and dehydrated bovine tannery sludge (10, 20, 30 and 40% sludge) and a conventional substrate of Conilon seedlings production. Levels of chromium were evaluated in different parts of seedlings and on biometric parameters of development, from planting the cuttings until 120 days. The plant organ, which most accumulated chromium in its tissues, was the roots, followed by the leaves and the stems. The pattern of seedlings vegetative growth was affected by the levels of silt in the substrate.